Environmental Stewardship Issue among Malaysian Manufacturing Firms - Mohamad Ghozali Bin Hassan; Norani Nordin; Hasbullah Ashari (International Journal of Supply Chain Management, 2016)
Since the fourth industrial revolution is embryonic also known as the automation and machine era, the issue of industrial waste and pollution have become more pressing. This is because manufacturing firms are known to have the highest pollution. It has made the issues of environmental stewardship vital for both developing and developed countries. However, the implementation of the concept of environmental stewardship differs from country to country and from one manufacturing firm to another. Notwithstanding, this issue is vital for the human environment. Therefore, this paper investigated the issue of environmental stewardship among Malaysian manufacturing firms. Data were collected from 104 manufacturing firms of various production types. The findings of this study revealed that environmental stewardship culture among Malaysian manufacturing firms is low. Thus, the study identified 18 strategic steps to improve environmental stewardship culture among Malaysian manufacturing firms. These identified strategies will contribute to ensuring sustainable manufacturing practices through which industries can improve the manufacturing practices in order to offset the negativity on the environment.